2017
DOI: 10.3390/children4050034
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of NAFLD Diagnosed in Childhood: A Single-Center Study

Abstract: Little is known regarding the subsequent course of non-alcoholic fatty liver disease (NAFLD) diagnosed in childhood. The objectives of this single-center study were to gather data on long-term health outcomes and to assess the feasibility of contacting former pediatric patients. In a large pediatric medical center, electronic records were searched to initially identify 162 former patients who had a liver biopsy between 2000 and 2010. Of these, 44 subjects met the criteria for age at follow-up (≥18 year) and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…These data reflect an earlier study, which also measured liver triglyceride content and showed that children with T2D were twice as likely to have hepatic steatosis compared with weight-matched normoglycemic controls [11]. Data from a third study showed that 18.2% of pediatric patients had T2D when they were diagnosed with NAFLD [30]. These 3 studies indicated that NAFLD is associated with youth-onset T2D.…”
Section: Hepatologysupporting
confidence: 70%
See 1 more Smart Citation
“…These data reflect an earlier study, which also measured liver triglyceride content and showed that children with T2D were twice as likely to have hepatic steatosis compared with weight-matched normoglycemic controls [11]. Data from a third study showed that 18.2% of pediatric patients had T2D when they were diagnosed with NAFLD [30]. These 3 studies indicated that NAFLD is associated with youth-onset T2D.…”
Section: Hepatologysupporting
confidence: 70%
“…Adolescent girls (14-19 years of age) with at least [11,29,30,44] -Mental health/psychiatry [34]: psychosis [36], depression [5,35], autism spectrum disorder [33], binge eating [37,38] 3 delayed menstrual cycles were 6.5 times more likely to develop impaired fasting glucose and T2D when they were young adults (19-24 years of age) than those who never had a delayed cycle [25]. Similarly, the broad symptom of irregular menses was present in 20.5% of girls with T2D, which appeared higher than prevalence rates for healthy populations [26].…”
Section: Less-known Comorbid Associations With Youth-onset T2dmentioning
confidence: 99%
“…The term NAFLD encompasses a range of disease severity from steatosis, defined as fat accumulation in at least 5% of hepatocytes, to nonalcoholic steatohepatitis, defined as steatosis with inflammation and hepatocyte ballooning. There are limited natural history data in children, but studies have shown that childhood NAFLD can result in cirrhosis, severe liver disease, and death . NAFLD is also strongly associated with cardiometabolic disease risk factors, such as prediabetes and type 2 diabetes and atherogenic dyslipidemia .…”
mentioning
confidence: 99%
“…Long-term nationally representative data in US adults having severe hepatic steatosis as well as elevated alanine aminotransferase (ALT), aspartate aminotransferase or gamma-glutamyl transferase were associated with increased liver disease mortality. 23 In adults, type 2 diabetes and cardiovascular disease are also frequent adverse clinical outcomes associated with NAFLD 24 and there are few data suggesting that increased incidence of type 2 diabetes is the most rapid adverse clinical outcome 17,25 in children. One of the most challenging knowledge gaps is the lack of longer term natural history information, which complicates benefit-risk determinations in the development of therapeutics for pediatric NAFLD.…”
Section: Defining At-risk Populationsmentioning
confidence: 99%